2007
DOI: 10.1016/j.bbrc.2007.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Genistein induces the metastasis suppressor kangai-1 which mediates its anti-invasive effects in TRAMP cancer cells

Abstract: Previous studies demonstrated a direct correlation with loss of kangai-1 (KAI1), a metastasis suppressor, and poor prognosis in human prostate and other cancers. In this study, we have characterized the age-dependent downregulation of KAI1 in the TRAMP model which was reversed when mice were fed a genistein-enriched diet. We demonstrated here that doses of genistein (5 and 10 μM) -which could be achieved by supplement intake-significantly induced the expression of KAI1, both at the mRNA and protein levels (up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…Interestingly, we also found that down-regulation of both NDRG1 and KAI1 already took place in the primary tumor in patients without metastasis, although it will be more obvious in metastatic patients. Consistently, El Touny et al (51) previously discovered an age-dependent down-regulation of KAI1 in the transgenic adenocarcinoma of the mouse prostate (TRAMP) mice model, which started from 24 weeks when the tumor developed but before metastasis occurred. We also found that Ndrg1 was down-regulated significantly in the hyperplasia stage of MMTV-Wnt1 and MMTV-neu transgenic mice (supplemental figure).…”
Section: Discussionsupporting
confidence: 54%
“…Interestingly, we also found that down-regulation of both NDRG1 and KAI1 already took place in the primary tumor in patients without metastasis, although it will be more obvious in metastatic patients. Consistently, El Touny et al (51) previously discovered an age-dependent down-regulation of KAI1 in the transgenic adenocarcinoma of the mouse prostate (TRAMP) mice model, which started from 24 weeks when the tumor developed but before metastasis occurred. We also found that Ndrg1 was down-regulated significantly in the hyperplasia stage of MMTV-Wnt1 and MMTV-neu transgenic mice (supplemental figure).…”
Section: Discussionsupporting
confidence: 54%
“…After obtaining these results with our combination diets, we next plan to test some of the compounds individually. Genistein (20,21), EGCG (22)(23)(24)(25)(26), resveratrol (27), and apigenin (28) have all been previously tested, and only high-dose genistein (250-500 mg/kg; ref. 21) has been reported to affect PDC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, genistein directly inhibited MEK4 kinase to decrease MMP-2 expression and the invasiveness in four prostate cancer cell lines, including PC3-M, PC3, 1532CPTX, and 1542CPTX [140]. Two doses of genistein, 5 and 10 μM, significantly induced the mRNA and protein levels of kangai-1 (KAI1), a metastasis suppressor, and decreased the invasiveness of TRAMP-C2 cells [141].…”
Section: Genisteinmentioning
confidence: 98%